2003
DOI: 10.1109/tac.2003.816965
|View full text |Cite
|
Sign up to set email alerts
|

Antiwindup for stable linear systems with input saturation: An LMI-based synthesis

Abstract: Abstract-This paper considers closed-loop quadratic stability and 2 performance properties of linear control systems subject to input saturation. More specifically, these properties are examined within the context of the popular linear antiwindup augmentation paradigm. Linear antiwindup augmentation refers to designing a linear filter to augment a linear control system subject to a local specification, called the "unconstrained closed-loop behavior." Building on known results on and LPV synthesis, the fixed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
356
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 488 publications
(369 citation statements)
references
References 30 publications
5
356
3
5
Order By: Relevance
“…This non-square sector condition is applied with the S-procedure [2] to the deferred-action AW problem proposed by [22]. The arising deferred-action AW synthesis conditions are much closer to those found in the standard ("immediate") case of [9]: the LMI's are of similar complexity, and contain the inequalities of [9] as special cases, unlike the LPV-based results in [22,26]; the increase in complexity as the number of control inputs increased is linear rather than polynomial (as for [22]). It will also be shown that the results derived here are less conservative than the sector-based results found in [26].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…This non-square sector condition is applied with the S-procedure [2] to the deferred-action AW problem proposed by [22]. The arising deferred-action AW synthesis conditions are much closer to those found in the standard ("immediate") case of [9]: the LMI's are of similar complexity, and contain the inequalities of [9] as special cases, unlike the LPV-based results in [22,26]; the increase in complexity as the number of control inputs increased is linear rather than polynomial (as for [22]). It will also be shown that the results derived here are less conservative than the sector-based results found in [26].…”
Section: Introductionmentioning
confidence: 66%
“…Many modern approaches to AW design are based on tools from convex optimisation ( [18,13,9,31,8,21,19,21,5,1,17]) and although these provide an attractive framework for AW synthesis, the compensators produced can be conservative: while stability is guaranteed, observed time-domain performance may be disappointing. This has two main sources: (i) the quadratic Lyapunov functions and sector bounds used in the synthesis algorithms; and (ii) the linearity of the AW compensator, which means its behaviour is identical for both small and large excursions beyond the control limits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O objetivo da compensação de anti-windup é o estabelecimento de uma correção automática dos estados do controlador, quando da ocorrência da saturação, a fim de minimizar a perda de performance ou maximizar a região de atração do sistema em malha fechada (ver (Kothare et al, 1994), (Grimm et al, 2003), (Gomes da Silva Jr. and Tarbouriech, 2005) e referências). Considerando o caso de estabilidade local, em (Hu et al, 2002), é proposta uma formulação baseada em inequações matriciais bilineares (BMIs) relaxadas utilizando um modelo politópico do termo de saturação.…”
Section: Introductionunclassified
“…Neste tipo de modelagem, a estrutura da condição de setor clássica é relaxada, permitindo a obtenção de condições diretamente na forma de LMIs. Resultados relativos a compensadores dinâmicos de anti-windup são apresentados em (Grimm et al, 2003), e . Do ponto de vista prático, o problema de seguimento de referências em sistemas com restrição de controle é de grande interesse.…”
Section: Introductionunclassified